MiR-107 Activates NF- κ B versus A β Analysis of the regulatory effect of 1-42 induced apoptosis in Alzheimer’s disease cells - Peng, Yihuai; Du, Zhen; Duan, Jianxiu; Shao, Yaqin; Nie, Shengdan (Cellular and Molecular Biology, 2023)
Alzheimer’s disease (AD) is one of the acute degenerative diseases of the brain that occurs in the central nervous system. This disease is caused by the abnormal deposition of insoluble plaques and peptide amyloid beta (Aβ), the formation of nodules, and synaptic disorder. The formation of these nodes disrupts the functioning of neural circuits and changes in behavioral response due to the activation of neurotransmitter receptors. Research in recent years has shown that microRNAs play an effective role in Alzheimer’s disease and neurotransmitter factors. Recently, miR-107 is effective in the pathology of Alzheimer’s disease (AD) through the regulation of NF-κB signaling pathway. Experiments conducted using the dual luciferase method and western blot analysis also showed that miR-107 in primary neurons affects neurotransmitter factors in Alzheimer’s disease through the regulation of the NF-κB signaling pathway. The results showed that the reduction of miR-107 expression through the regulation of the NF-κB signaling pathway leads to the suppression of cell apoptosis in Alzheimer’s patients. On the other hand, increasing the expression of miR-107 leads to increasing the breaking process of Amyloid precursor protein (APP). This factor increases the production of amyloid beta (Aβ) peptide plaques and increases the expression of the BACE1 gene, which ultimately leads to the induction of apoptosis and induction of Alzheimer’s disease.